2020
DOI: 10.5435/jaaos-d-20-00763
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Practice Patterns of Conventional and Computer-assisted Knee Arthroplasty: An Analysis of 570,671 Knee Arthroplasties Between 2010 and 2017

Abstract: Background: Despite advances in computer-assisted knee arthroplasty (CAKA), little is known about the uptake of this technology in recent years. We aimed to explore the utilization trends and practice variation of CAKA from 2010 to 2017 and investigate the predictors of CAKA adoption. Methods: Patients undergoing conventional knee arthroplasty and CAKA were identified from the states of New York and Florida's administrative databases using the Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Surprisingly, the annual proportion of TKAs performed using technology within the NSQIP database decreased from 2010 to 2018. A recent study found that the utilization of computer-assisted TKA increased from 4.9% to 9.5% in New York and from 4.0% to 5.7% in Florida between the years 2010 and 2017 [ 14 ]. An NIS database analysis found that the proportion of TA-TKA increased steadily from 1.2% in 2005 to 7.0% in 2014 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, the annual proportion of TKAs performed using technology within the NSQIP database decreased from 2010 to 2018. A recent study found that the utilization of computer-assisted TKA increased from 4.9% to 9.5% in New York and from 4.0% to 5.7% in Florida between the years 2010 and 2017 [ 14 ]. An NIS database analysis found that the proportion of TA-TKA increased steadily from 1.2% in 2005 to 7.0% in 2014 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although TA-TKA has been available for several decades, TA-TKA has not been universally adopted [ 12 ] and accounts for only 5–10% of TKAs performed in the USA [ 13 , 14 ]. This low utilization rate may be attributable to costly capital investment for hospital systems, increased operative times, a significant learning curve alongside training burden, and skepticism from operators who have already achieved quality outcomes utilizing unassisted techniques [ 15 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary variable of interest was the use of computer-assisted navigation technology. 8 9 10 11 12 13 14 Covariates included age 21 and insurance type, 22 as well as the Charlson Comorbidity Index, which was applied to clinical comorbidity data to calculate a measure of disease burden. 23 - 25 Race/ethnicity was also included as a covariate because of its known effect on patient access and other outcomes.…”
Section: Methodsmentioning
confidence: 99%
“… 23 - 25 Race/ethnicity was also included as a covariate because of its known effect on patient access and other outcomes. 14 , 26 - 28 Finally, we adjusted for hospital volume, which was defined using quartiles of combined 2-year procedure volume. 29 , 30 Odds ratios (ORs) and their 95% confidence intervals (95% CIs) were estimated and reported, and all P values were two-sided with statistical significance evaluated at an alpha level of <0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation